There is hope for a tree : the tree as metaphor in Isaiah - Nielsen, Kirsten, 1943- (Journal for the study of the Old Testament. Supplement series, 1989)
Insights gained from the study of metaphorical language in other fields, particularly New Testament parable research, are here applied to the tree metaphors in Isaiah 1-39. The focus of investigation is the content of the metaphors, the intentions underlying their use, and the consequences of that use. The author suggests that (1) the informative function of the tree metaphors is to provide theological interpretations of the political situation; (2) the performative function of the metaphors is to engage the audience in such a way that they adopt the metaphors' interpretation of reality as th.